The Importance of Fetal Station in the First Stage of Labor - Jones, Sara I.; Imo, Chinonye S.; Zofkie, Amanda C.; Ragsdale, Alexandra S.; Mcintire, Donald D.; Nelson, David B. (American Journal of Perinatology, 2024)
Objective This study aimed to examine the relationship of fetal station in the first stage of labor to labor curves and cesarean delivery rates among women presenting in spontaneous labor.Study Design Labor curves for patients with nonanomalous singletons who presented in spontaneous labor to our hospital's Obstetric Triage Unit with intact membranes from January 1, 2012, to August 31, 2016, were reviewed. Cervical exams and time of exam were obtained for each patient from presentation to triage until delivery. Station for each presentation and cervical dilation was estimated using a random effects model and the slope of cervical station change was calculated to estimate the change in dilation by hour. Perinatal outcomes, including cesarean delivery rates, were examined according to fetal station at initial presentation. Factors known to affect labor curves—epidural analgesia, infant birth weight, maternal habitus, and parity—were also examined.Results There were 8,123 patients presented in spontaneous labor with intact membranes. For patients presenting at 6-cm dilation, the rate of change of labor was significantly different when identified to have a station greater than 0 (+1 and more caudad) when compared with those with −1 and more cephalad station (both p < 0.001). This relationship persisted when analyzed according to epidural analgesia, birth weight, maternal habitus, and parity. The frequency of cesarean delivery was significantly higher for women presenting in spontaneous labor with negative fetal station (p < 0.05). When stratified across all dilation (3–9 cm), this trend remained significant (p < 0.001).Conclusion In the first stage of labor, advanced fetal station was significantly associated with differing rates of labor progression, and positive fetal station was significantly less likely to result in cesarean delivery. Physical examination, including station, remains a critical element in labor management.Key Points
Keywords: cervical exam; cesarean delivery; fetal station; labor curve; labor management; perinatal outcomes